2019
DOI: 10.2478/cipms-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dissolution studies on granules with acetaminophen and caffeine using the basket and paddle methods with simultaneous spectrophotometric determination of active substances

Abstract: Acetaminophen and caffeine, popular therapeutic substances used to relieve pain or alleviate the symptoms of cold. The aims of the study were the comparison of granules, in terms of dissolution rate and moreover the development of spectrophotometric method to the simultaneous determination of both active pharmaceutical ingredients (APIs) in granules. The granules were tested by two pharmacopoeial methods of dissolution for solid dosage forms, and the dissolution profiles for each formulation were compared. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Some authors have studied the UV identi ication of ACE/CAF in granules (Szumilo et al, 2019), and in commercial tablets (Dinç, 1999;Vichare et al, ). These methods used simultaneous equations to quantify both drugs without mutual interference.…”
Section: Dissolution Pro Ilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have studied the UV identi ication of ACE/CAF in granules (Szumilo et al, 2019), and in commercial tablets (Dinç, 1999;Vichare et al, ). These methods used simultaneous equations to quantify both drugs without mutual interference.…”
Section: Dissolution Pro Ilesmentioning
confidence: 99%
“…These methods used simultaneous equations to quantify both drugs without mutual interference. In granules, more than 80% of ACE and CAF were released in less than 10 min (Szumilo et al, 2019) and both analytical methods reported for commercial tablets can be used for quality control purposes. Especially in dissolution studies, controlled release of CAF tablets has been reported by some authors (Franek et al, 2014;Tan et al, 2019) and more than 80% of drug dissolved was found between 20-24 h. On the other hand, more than 80% of CAF at 20 min was found in immediaterelease formulations with a binary mixture of drugs and HPLC determination (Williams et al, 2010) as well as with a ternary mixture (Liu et al, 1999).…”
Section: Dissolution Pro Ilesmentioning
confidence: 99%